The Indonesia Stock Exchange's Banking Company Share Price Influencing Factors - Diana Dwi Astuti; Hamzah Fansuri Yusuf (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2023)
This study aims to determine the effect of interest rates, inflation, profitability and liquidity on stock prices in banking companies on the Indonesia Stock Exchange (IDX) 2017-2021. The type of research used is quantitative research. The data used in this study are secondary data obtained from a collection of literature books, accounting journals and financial data of banking companies listed on the Indonesia Stock Exchange (IDX). The data processing method used multiple linear analysis method with the help of SPSS 22 analysis tool. The results showed that partially the profitability variable had a significant effect on stock prices. Meanwhile, the interest rate, inflation and liquidity variables partially have no effect on stock prices. Simultaneously interest rates, inflation, profitability and liquidity have a significant effect on stock prices.